Estudio de pre-factibilidad para la producción tecnificada de vino de mortiño (Vacciniumfloribun dumkunth) en el cantón Sigchos comunidad Quinticusig Asociacion de vinicultores período 2012-2013 - Albán Martínez, Darwin Patricio (2013)
This pre -feasibility study for the modern production of mortiño wine Vacciniumfloribun dumkunth ) in the winemakers association froom Sigchos cantón, Quinticusig town during the years 2012- 2013 " , was held because of the request of the Ministry of Agriculture, Livestock , Aquaculture and Fishing from Cotopaxi Province. In order to give more value to the production of mortiño, new technology to give more and new production alternatives to the winemakers has been proposed. These alternatives are sustainable and sustainable and they will not generate negative effects that affect the biodiversity and to the population. Within the research process were conducted marketing studies, technical and economic factors involved in industrial development such as: land, raw materials, capital, labor and the potential environmental impact generated by the wine factory. Then, it was possible to know the total investment of $ 54,953.80. All this was done by using the research field techniques. Scientific observation and a survey was used to collect the data which was analyzed and presented graphically.